Effect of socio-economic status on performance of women owned Small and Medium Enterprises in Nairobi - Njenga, L. (Strathmore University, 2024)
Globally, small and medium enterprises (SMEs) have a significant impact on the economic and social development of nations, particularly in developing countries. However, it is important to note that the ownership of these businesses is predominantly male dominated, leading to socioeconomic status for women in entrepreneurship activities. Therefore, the objective of this current study is to examine the influence of socioeconomic status on the performance of women-owned SMEs in Nairobi City County. Specifically, the study focuses on socio-cultural status, economic status, and demographic status and their impact on the performance of women-owned SMEs. The study is guided by empowerment theory and complemented by the resource-based view theory. The research was carried out using a descriptive cross-sectional survey design to gather the necessary data for analysis. A total of 14,232 registered women-owned SMEs across the 17 sub-counties in Nairobi County as participants. The sample size of 389 respondents was determined using the Yamane formula and stratified random sampling technique was used to distribute the sample across the sub-sectors. Primary data was collected through a questionnaire, and the collected data was analyzed using the Statistical Package for the Social Sciences (SPSS). The analysis included both descriptive and inferential statistics, with multiple linear regression analysis and correlation analysis being conducted as part of the inferential statistics. The study findings were presented and interpreted using frequency tables and figures. The finding of the study established that there existed a positive and significant relationship between socio-cultural status, economic status, demographic status and performance of women-owned small and medium enterprises in Nairobi City County. Future studies should explore the specific mechanisms through which socioeconomic status affect women-owned SMEs. This could involve examining the role of education, social networks, and cultural norms in shaping women entrepreneurs' access to resources and opportunities. Understanding these underlying mechanisms would provide valuable insights for designing targeted interventions to address the challenges faced by women-owned SMEs.
Full - text thesis